A study of summer and winter highly time-resolved submicron aerosol composition measured at a suburban site in Prague. (October 2015) - Kubelová, Lucie; Vodička, Petr; Schwarz, Jaroslav; Cusack, Michael; Makeš, Otakar; Ondráček, Jakub; Ždímal, Vladimír
Abstract: The variability of aerosol chemical composition and the impact of the origin of respective air masses were studied in high time resolution for selected periods of high and low levels of aerosol burden at a suburban station in Prague-Suchdol, Czech Republic in summer and winter. Ambient aerosol measurements were performed using the compact-Time of Flight-Aerosol Mass Spectrometer (c-ToF-AMS) and variations in concentration of the main species are discussed. The average mass concentrations for the main species were (summer; winter): organic matter (4.2 μg/m 3 ; 8.4 μg/m 3 ), SO 4 2 − (2.0 μg/m 3 ; 4.4 μg/m 3 ), NH 4 + (1.2 μg/m 3 ; 2.8 μg/m 3 ), NO 3 − (0.8 μg/m 3 ; 5.4 μg/m 3 ) and Cl − (0.1 μg/m 3 ; 0.23 μg/m 3 ). We found an inverse relationship between non-refractory submicron particulate matter (NR-PM1 ) levels and the boundary layer height, mainly in winter. Furthermore, levels of pollution were influenced by the air mass origin, where cleaner maritime air masses resulted in lower aerosol levels compared to those of continental origin. Analysis of the diurnal variation of NR-PM1 showed minimum concentrations in the afternoon caused by dilution as a result of an increase in the boundary layer height. Most maximum concentrations of the main species occurred in the morning or night except sulphate which had a midday maximum, probably due to downdraft from upper boundary layer air and photochemical formation in the afternoon. Highlights: Atmospheric aerosol NR-PM1 was measured by c-ToF-AMS at a suburban site in Prague. High time-resolution enabled detailed description of daily cycles of pollutants. Size distribution of fine mode was described in both summer and winter. Analysis of organic fragments proved influence of wood combustion in winter. Atmospheric aerosol NR-PM1 was less oxygenated in winter than in summer.